Automatic identification and quantification of safety risks embedded in design stage: a BIM-enhanced approach - Xiahou, Xiaer; Li, Kang; Li, Funing; Zhang, Zhenqi; Li, Qiming; Gao, Yuan (Journal of Civil Engineering and Management, 2022)
Design stage plays a decisive role in safety risk management of the whole life cycle for construction projects. However, existing research mostly pay attention to post-accident management and lack pre-management consciousness. Based on the concept of design for safety (DFS), this paper explains how design optimization can enhance the safety performance for construction projects. Firstly, use accident causality theory and trajectory crossing theory to clarify the logical relationship between safety accidents and design process. Then, identify risk sources of safety accidents in deep foundation pit of subway projects and form a safety management knowledge base. Thirdly, based on design and review rules in the knowledge base and improved FEC risk quantification method, quantify the design oriented subway construction safety risks. Finally, use BIM secondary development technology to realize automatic examination and visualization of safety risks. A case study was conducted to verify this research framework. This paper can be a supplement to the existing risk management theoretical research.